The Lung, the Heart, the Novel Coronavirus, and the Renin-Angiotensin System; The Need for Clinical Trials - Lumbers, Eugenie R.; Delforce, Sarah J.; Pringle, Kirsty G.; Smith, Gary R. (Frontiers in Medicine, 2020)
Angiotensin-converting enzyme 2 (ACE2) is the receptor for COVID-19 (SARs-CoV-2). ACE2 protects the lung and heart from acute respiratory distress syndrome (ARDS) and acute myocarditis and arrhythmias, because it breaks down Angiotensin II, which has inflammatory effects in the lung and heart as well as in the kidney. When COVID-19 binds to ACE2 it suppresses it, so this protective action of ACE2 is lost. Death from COVID-19 is due to ARDS and also heart failure and acute cardiac injury. Drugs that prevent the inflammatory actions of Angiotensin II (i.e. Angiotensin receptor blocking drugs, ARBs) prevent acute lung injury caused by SARS-CoV. A clinical trial is underway in the USA (https://clinicaltrials.gov/ct2/show/NCT04312009) to test the risks and benefits of an ARB in COVID-19 patients requiring hospitalisation. Other potential treatments are also discussed.